The fields - Young, Erin, 1975- (Flatiron Books, 2022)
"A breakneck procedural that is beautifully written and masterfully crafted, Erin Young's The Fields is a dynamite debut-crime fiction at its very finest. Some things don't stay buried. It starts with a body-a young woman found dead in an Iowa cornfield, on one of the few family farms still managing to compete with the giants of Big Agriculture. When Sergeant Riley Fisher, newly promoted to head of investigations for the Black Hawk County Sheriff's Office, arrives on the scene, an already horrific crime becomes personal when she discovers the victim was a childhood friend, connected to a dark past she thought she'd left behind. The investigation grows complicated as more victims are found. Drawn deeper in, Riley soon discovers implications far beyond her Midwest town"--